Future Financial Decisions Influencing Factors - Irwan Moridu; Nurcahya Hartaty Posumah; Fitriani Fitriani; Asri Ady Bakri; Yusni Yusni (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to pinpoint the variables that affect how people make financial decisions in the future. Future financial decisions, saving choices, and trust in banking institutions are the three variables we use in this study. 197 junior high school teachers from the Bandung region participated in the study. Multivariate Regression is the analytical approach used, and it can be used to assess the influence of independent variables on dependent variables. The results demonstrate a strong positive relationship between current saving decision variables and future financial decision variables. Similar to this, varying levels of trust in financial organisations have a lot of favourable effects. These findings imply that people have a greater propensity to save when they are motivated to do so. People who have confidence in financial institutions will manage their money prudently going forward.